ChamelIoT: An agnostic operating system framework for reconfigurable IoT devices - Silva, Miguel (2019)
This letter proposes ChamelIoT, an agnostic operating system (OS) framework for reconfigurable Internet of Things (IoT) devices. ChamelIoT is bringing a reconfigurable hardware OS stack supported by a semantically enriched infrastructure that aims at offering an easy-to-use tool for building (mainly) low-power and low-cost IoT sensors with performance, real-time, and power consumption advantages.